Demand for pre-exposure prophylaxis for HIV and the impact on clinical services: Scottish men who have sex with men perspectives. (March 2018) - Gilson, RI; Clutterbuck, DJ; Chen, ZE
There is a lack of data on ability and willingness of men who have sex with men (MSM) to self-fund HIV pre-exposure prophylaxis (PrEP). We aimed to explore how many eligible (PROUD study criteria) men may want PrEP and how many lower-risk MSM would be willing and able to self-fund this intervention. A self-completed anonymous questionnaire was distributed to MSM populations attending services. Of 377 participants, 81.5% were aware of PrEP. Fifty-three (15.5 %) were eligible, of whom 43 (81%) were very/extremely likely to want it. Of those ineligible, 229 (80%) were aware of PrEP and 106 (37.3%) were very/extremely likely to want it. Of eligible respondents 23% would be willing and able to pay at least £50 a month for PrEP. Of ineligible respondents this proportion was 21%. Our survey revealed high levels of awareness, understanding and willingness to take PrEP among MSM at high and lower risk of HIV acquisition. It indicated that over 70% of high-risk men would be unwilling or unable to self-fund PrEP, should it not be available on the NHS. For lower-risk MSM we estimated that capacity requirements for monitoring self-funded PrEP will be 50% higher than numbers eligible for PrEP. These factors will need to be taken into account when planning services.